Determinants of Sustainable Land Use Change in Agricultural Utilization and Environmental Performance - Anggono, Bayu Dwi; Wahanisa, Rofi; Melina, Cairin (International Journal of Energy Economics and Policy, 2023)
This paper aims to analyze the determining factors in the use of sustainable agro-industry by implementing renewable energy and environmental management performance. The paper also aims to investigate environmental policies carried out by the local government to minimize land-use conversion of agricultural utilization to non-agricultural functions. This study uses a data driven empirical approach in examining agro-industrial utilization in land-use conversion in Boyolali, Indonesia. The nature of the study was by employing sociology of law to analyze policy aspects in social interactions in environmental performance and sustainability ideas in land-use coversion cases. The results of the study show that the orientation of economic growth by implementing a renewable system and preserving agricultural land is the basis for regional policies to protect agricultural land. The findings also highlight spatial planning as the most important aspect in technical implementation of sustainability pratices in the cases of land-use conversion to non-agricultural functions. The findings would imply the need for optimization and control of agricultural land protection through environmentally-friendly local policies to control land-use conversion and maintain sustainable functions of land. The findings also imply to the importance of environmentally-friendly policies ranging from preparation of regulations, determination of regional spatial plans, environmental permits, and incentives in managing sustainability of environmental performance in land-use policy in local context.